Structure-based mechanism of cysteinyl leukotriene receptor inhibition by antiasthmatic drugs - Luginina, Aleksandra; Gusach, Anastasiia; Marin, Egor; Mishin, Alexey; Brouillette, Rebecca; Popov, Petr; Shiriaeva, Anna; Besserer-Offroy, Élie; Longpré, Jean-Michel; Lyapina, Elizaveta; Ishchenko, Andrii; Patel, Nilkanth; et al. (Science advances, 2019)
The G protein-coupled cysteinyl leukotriene receptor CysLT1R mediates inflammatory processes and plays a major role in numerous disorders, including asthma, allergic rhinitis, cardiovascular disease, and cancer. Selective CysLT1R antagonists are widely prescribed as antiasthmatic drugs; however, these drugs demonstrate low effectiveness in some patients and exhibit a variety of side effects. To gain deeper understanding into the functional mechanisms of CysLTRs, we determined the crystal structures of CysLT1R bound to two chemically distinct antagonists, zafirlukast and pranlukast. The structures reveal unique ligand-binding modes and signaling mechanisms, including lateral ligand access to the orthosteric pocket between transmembrane helices TM4 and TM5, an atypical pattern of microswitches, and a distinct four-residue-coordinated sodium site. These results provide important insights and structural templates for rational discovery of safer and more effective drugs.
Keywords: Receptors, Leukotriene; Protein Structure, Tertiary; receptory leukotrienů; tosylové sloučeniny; Indoles; Leukotriene Antagonists; ligandy; simulace molekulového dockingu; Phenylcarbamates; chromony; lidé; krystalografie rentgenová; rekombinantní proteiny; sulfonamidy; Molecular Docking Simulation; Crystallography, X-Ray; Chromones; Ligands; vazebná místa; Sulfonamides; Humans; Binding Sites; Tosyl Compounds; sodík; indoly; fenylkarbamáty; Anti-Asthmatic Agents; Sodium; terciární struktura proteinů; antiastmatika; antagonisté leukotrienů; Recombinant Proteins